Exploring the neural basis of non-invasive prehabilitation in brain tumour patients: An fMRI-based case report of language network plasticity - Boccuni, Leonardo; Roca-Ventura, Alba; Buloz-Osorio, Edgar; Leno-Colorado, David; Martín-Fernández, Jesús; Cabello-Toscano, María; Perellón-Alfonso, Ruben; Pariente Zorrilla, Jose Carlos; Laredo, Carlos; Garrido, Cesar; Muñoz-Moreno, Emma; Bargalló, Nuria; et al. (Frontiers in Oncology, 2024)
Primary brain neoplasms are associated with elevated mortality and morbidity rates. Brain tumour surgery aims to achieve maximal tumour resection while minimizing damage to healthy brain tissue.Research on Neuromodulation Induced Cortical Prehabilitation (NICP) has highlighted the potential, before neurosurgery, of establishing new brain connections and transfer functional activity from one area of the brain to another. Nonetheless, the neural mechanisms underlying these processes, particularly in the context of space-occupying lesions, remain unclear. A patient with a left frontotemporoinsular tumour underwent a prehabilitation protocol providing 20 sessions of inhibitory non-invasive neuromodulation (rTMS and multichannel tDCS) over a language network coupled with intensive task training. Prehabilitation resulted in an increment of the distance between the tumour and the language network. Furthermore, enhanced functional connectivity within the language circuit was observed. The present innovative case-study exposed that inhibition of the functional network area surrounding the space-occupying lesion promotes a plastic change in the network's spatial organization, presumably through the establishment of novel functional pathways away from the lesion's site. While these outcomes are promising, prudence dictates the need for larger studies to confirm and generalize these findings.